Intravenous immunoglobulin induced pancytopenia while preventing development of gestational alloimmune liver disease: A case report - Minhazur Sarker; Chelsea DeBolt; Noel Strong (Elsevier, 2022)
Gestational alloimmune liver disease is a rare complication associated with reactive maternal immunoglobulins resulting in neonatal liver pathology. The mainstay treatment for prevention in future pregnancies is intravenous immunoglobulins. Although relatively well tolerated, adverse reactions may occur. In this report, we highlight a case of intravenous immunoglobulin induced pancytopenia diagnosed by exclusion after thorough work-up. The patient was counseled on options and an informed decision was made to proceed with re-trial of intravenous immunoglobulin without systemic prednisone. This resulted in the delivery of a healthy neonate. We propose that future adverse reactions to intravenous immunoglobulin in pregnancy may warrant the trial of a new medication lot and use of systemic steroids only if subsequently indicated.